D. MOVILLA - 99 Years of the Housing Question in Sweden - Campaña, Esperanza (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2019)
Daniel Movilla Vega (ed.) 99 Years of the housing question in Sweden Based on an ArkDes exhibition curated by Dan Hallemar Lund: Studentlitteratur, 2017. 325 pages. Softcover. Language: English ISBN-10: 9144120478. ISBN-13: 978-9144120478